Macroeconomic Volatility and Bank Lending Behavior: An ARDL Approach Using Indonesian Time-Series Data - Lestari, Fitriana Dwi; Wijaya, Hendra (CV. Global Cendekia Inti, 2025)
This study investigates the impact of macroeconomic volatility on bank lending behavior in Indonesia using the Autoregressive Distributed Lag (ARDL) approach. Macroeconomic fluctuations, particularly in inflation, exchange rates, and interest rates, create uncertainties that affect banks’ lending decisions. This study utilizes annual time-series data from 2000 to 2023 and analyzes the dynamic relationship between selected macroeconomic indicators and total bank credit. The findings reveal that inflation volatility and exchange rate fluctuations negatively impact bank lending in both the short and long run, while GDP growth positively influences credit expansion. Interest rate volatility shows a weaker but still significant short-run effect. These results imply that macroeconomic stability is essential for fostering credit growth in Indonesia. Policymakers are advised to maintain a predictable macroeconomic environment to support financial intermediation and sustainable economic development.